PENGARUH SUDUT BUKAAN GUIDE VANE DAN TEKANAN AIR TERHADAP KECEPATAN PUTAR DAN DAYA OUTPUT PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DENGAN TURBIN CROSSFLOW - Arta Wijaya, I Wayan; Dwi Mertadiyasa, I Made; Suartika, I Made (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p19, 2020)
The pattern of power plants development in Indonesia is still relying on the availability of fossil fuels based energy sources. Meanwhile, Human are faced with a situation of depleting reserves of fossil energy sources and increasing environmental damage due to the use of fossil fuels based energy sources. Renewable Energy development can be a solution to these problems. One of them is the development of a Micro Hydro Power Plant. In the realization of Micro Hydro Power Plant in Indonesia, the crossflow water turbine type can be used. It is a type of impulse turbine with a good characteristic at a low head for micro-scale generator capacity. This study analyzes the effect of guide vane opening angle and water pressure on rotation and output power of crossflow turbine. The opening angle of the guide vane studied was 15º, 30º, 45º, 60º, 75º, and 90º in each water pressure condition of 4 psi, 8.5 psi and 13 psi. The test is carried out by simulating direct measurements on the prototype of the Micro-hydro Power Plant that has been built. Every combination of parameters tested, the maximum value of rotational speed and output power is obtained at the guide vane opening angle of 30º and water pressure of 13 psi. Turbine rotation values generated before and after coupled with a generator are 591.9 rpm and 522.7 rpm. The values of the generator rotation before and after the load coupled are at 3490 rpm and 2368 rpm. And the power value generated by the generator is 11.8 Watts.